DEVELOPMENT OF ORGANISATIONAL COMPETENCIES DURING TRANSITION AND ADAPTATION TO INDUSTRY 4.0. (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Competencies that enable organizations to effectively implement digital technologies and provide them with the ability to adapt to changes in the digital environment can be classified as organizational competencies in the context of digital transformation. During the transition to Industry 4.0, organizations find themselves in conditions of a high level of uncertainty and complexity, which requires them to adapt to the new context. A key factor in this process is competencies that ensure high competitiveness and innovative potential. However, the scientific literature does not sufficiently disclose their content, classification levels, and development opportunities under digitalization conditions. This article attempts to fill this gap by analyzing the impact of new technologies on organizational competencies. A conceptual model is presented, which is based on the assumption that the degree of digitalization strengthens the interaction of higher-level competencies - strategic flexibility and ambidexterity.